Revision of Simulium rufibasis (Diptera: Simuliidae) in Japan and Korea: Chromosomes, DNA, and Morphology. Issue 2 (20th November 2019) - Adler, Peter H; Fukuda, Masako; Takaoka, Hiroyuki; Reeves, Will K; Kim, Sam-Kyu; Otsuka, Yasushi
Abstract: The widespread nominal black fly Simulium ( Simulium ) rufibasis Brunetti was reexamined morphologically, chromosomally, and molecularly to determine the status of populations in Japan and Korea with respect to S. rufibasis from the type locality in India and to all other known species in the S. ( S. ) tuberosum species-group. Morphological comparisons established that the species previously known as S. rufibasis in Japan and Korea is distinct from all other species. Consequently, it was described and illustrated as a new species, Simulium ( S. ) yamatoense . Simulium yokotense Shiraki, formerly a synonym of S. rufibasis, was morphologically reevaluated and considered a species unplaced to species-group in the subgenus Simulium . Chromosomal analyses of S. yamatoense sp. nov. demonstrated that it is unique among all cytologically known species of the S. tuberosum group and is the sister species of the Taiwanese species tentatively known as S . ( S .) arisanum Shiraki. Populations of S. yamatoense sp. nov. included two cytoforms, based on the sex chromosomes. Cytoform A, including topotypical representatives, was found in Kyushu, Japan, whereas cytoform B was found in Korea and Honshu, Japan. Molecular analysis based on the COI mitochondrial gene generally corroborated morphological and chromosomal data that S. yamatoense sp. nov. is a distinct species and, like the chromosomal data, indicate that it is most closely related to S. arisanum, with interspecific genetic distance of 2.92–4.63%.